PIE statutory audit market concentration: evidence from Latvia - Saksonova, Svetlana; Rozgina, Ludmila (University of Latvia, 2019)
The reform of EU audit legislation was adopted by the Council of the EU in April 2014. The legislation consists of an audit Directive and an audit Regulation. The Directive applies to all statutory audits; the Regulation contains specific requirements for the statutory audits of public-interest entities (PIEs). The Regulation aims both at enhancing audit quality and at promoting competition in the audit market. Mandatory rotation, together with the incentives for joint audit and tendering, as well as the prohibition of certain non-audit services to audit clients - requiring de facto that another audit firm provides these services - are examples of measures that should make the market more dynamic and ultimately less concentrated. The purpose of this study is to assess the concentration levels in the market for statutory audits of PIEs in Latvia. The methods of the research are systematic, logical and comparative analysis, analysis of secondary data, as well as expert method. Data on market shares is analyzed using the four firm concentration indicators. The principle results of the study provide evidences about the high level of Latvia's PIE audit firms/networks market concentration, the dominant share of non-audit revenue in total revenue for the 6 biggest market players, the auditing oligopoly in the PIE market, the impact of the EU audit reform on the auditor-client relationships in the banking sector. Based on the findings and results of the study, the authors propose a set of recommendations aimed to make the Latvian audit market more transparent and less concentrated.
Keywords: audit market; audit market concentration; audit firms; public-interest entities; Research Subject Categories::SOCIAL SCIENCES::Business and economics